Neurodevelopmental outcome for offspring of women treated for antenatal depression: a systematic review - Previti, Giovanni (Arch Womens Ment Health, 2014)
The aim of this systematic review is to appraise existing literature on the effects of treatments for antenatal depression on the neurodevelopment outcomes of the offspring. We conducted a systematic review of the literature to identify studies on different kinds of treatments for antenatal depression (antidepressants and alternative therapies) and their effects on infants’ neurodevelopment. After reading the title, abstract, or full text and applying exclusion criteria, a total of 22 papers were selected. Nineteen papers studied the effects of antidepressant drugs, one on docosahexanoic acid (DHA) (fish oil capsules) and two on massage therapy; however, no studies used a randomized controlled design, and in most studies, the control group comprise healthy women not exposed to depression. Comparisons between newborns exposed to antidepressants in utero with those not exposed showed significant differences in a wide range of neurobehavioral outcomes, although in many cases, these symptoms were transient. Two studies found a slight delay in psychomotor development, and one study found a delay in mental development. Alternative therapies may have some benefits on neurodevelopmental outcomes. Our review suggests that antidepressant treatment may be associated with some neurodevelopmental changes, but we cannot exclude that some of these effects may be due to depression per se.